Implementation of Green Human Resource Management (GHRM) Toward A Sustainable Green Hospital: Bibliometric Mapping and Systematic Literature Review - Muhammad Ilham Surya Samawa; Putri Shela Sabila; Larasati Restu Dewayani; Nasiroh Nasiroh; Kosasih Kosasih; Vip Paramarta (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the development of Green Human Resource Management (GHRM) research and its contribution to Sustainable Green Hospital implementation, organizational sustainability, and sustainability-oriented employee behavior. It maps research trends and thematic structures, identifies relevant theories and GHRM practices, and explores managerial implications and future research directions. Research Design and Methodology: The study employed Bibliometric Analysis and a Systematic Literature Review following the PRISMA protocol. Articles were collected from Google Scholar, ScienceDirect, and Wiley Online Library using keywords related to GHRM, Sustainable HRM, Green Hospitals, and organizational sustainability. Thirty eligible articles were analyzed using VOSviewer and thematic synthesis. Findings and Discussion: GHRM publications have increased substantially. Dominant themes include organizational sustainability, environmental performance, employee green behavior, and sustainable HRM. The main theoretical foundations are Resource-Based View, Ability-Motivation-Opportunity Theory, Stakeholder Theory, and Sustainable HRM Theory. Green recruitment, training, performance appraisal, compensation, and employee participation were identified as key practices supporting Sustainable Green Hospitals. However, integrated research on GHRM and Sustainable Green Hospitals remains limited. Implications: Hospitals should integrate environmental objectives into HR policies, workforce development, and organizational culture. Future research should examine healthcare-specific contexts, longitudinal designs, green culture, environmental leadership, digital transformation, and employee green behavior.